2021
DOI: 10.1093/neuonc/noab303
|View full text |Cite
|
Sign up to set email alerts
|

Long-term natural history and patterns of sporadic vestibular schwannoma growth: A multi-institutional volumetric analysis of 952 patients

Abstract: Background The current study aims to characterize the natural history of sporadic vestibular schwannoma volumetric tumor growth, including long-term growth patterns following initial detection of growth. Methods Volumetric tumor measurements from 3,505 serial MRI studies were analyzed from unselected consecutive patients undergoing wait-and-scan management at three tertiary referral centers between 1998 and 2018. Volumetric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…These reliability measurements parallel previous published data (20). Lastly, we previously reported that the clinical features across the three institutions were similar (12). For these reasons, we believe that the methodology used in the current study is valid.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These reliability measurements parallel previous published data (20). Lastly, we previously reported that the clinical features across the three institutions were similar (12). For these reasons, we believe that the methodology used in the current study is valid.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, rather than embarking on observation to "see if the tumor grows," it should instead be assumed at the outset of wait-and-scan management that all vestibular schwannomas grow during a patient's lifetime. This claim can be intuited by appealing to the sporadic development of these tumors (i.e., people are not born with sporadic vestibular schwannomas, and each tumor must have grown to the size it is at the time of detection), and the claim is further supported by the recognition that most (80%) tumors show some degree of growth during extended MRI surveillance (12). Taken together, when pursuing wait-and-scan management in sporadic vestibular schwannoma, rather than reflexively treating all patients who demonstrate tumor growth, detection of tumor growth must only represent one factor among many that influences the decision to pursue definitive treatment, recognizing that the likelihood of future growth depends on factors such as the magnitude of previous growth and the recognition that small changes in tumor size bear little impact on patient outcomes during treatment (12,18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations